Annual plant reviews, Volume 21: Endogenous Plant Rhythms - Hall, Anthony J. W (Blackwell, 2012)
"Our knowledge of the circadian clock in plants has advanced considerably in recent years and we now have a clearer view of the biochemical processes making up its mechanism. Recent work provides insight into the central role played by the circadian system in the regulation of many aspects of metabolism. The multiple systems involved in photoreception have been determined, leading to an understanding of how light